Agency through Hindu spirituality in K.S. Maniam's The Return - Awang, Mohammad Ewan; Omar, Noritah (Universiti Putra Malaysia Press, 2016)
Hinduism plays an integral role in the Malaysian Indian identity construction. Its philosophical and spiritual tenets provide a crucial epistemic understanding of selfhood and existence to the Malaysian Indians for them to live a meaningful and flourishing life. Nonetheless, there is a perceived lack of discussion on the transformative role of Hinduism to the Malaysian Indians. The existing body of research predominantly views Hinduism as an outward representation of the Malaysian Indian identity through its religious festivals, rituals, and ceremonies. Hinduism is deemed to either exacerbate their sense of alienation and marginalization in Malaysia or reiterate the community’s nostalgic longing for Mother India. In this line of thought, religion is said to lack the capacity to grant agency to the Malaysian Indians. This article explores how these views are challenged by K.S. Maniam, a Malaysian Indian author who explores the transformative capacity of Hindu philosophy and spirituality to the Indian community in his literary works. Using Maniam’s first novel, The Return (1982), this article explores the transformative role of spirituality in bestowing the Malaysian Indians an alternative form of agency. Maniam’s narrative strategies reflect the Indian philosophy, Advaita Vedanta which stresses on the concept of “oneness” and the obliteration of the self-other and subject-object duality. Indian philosophy of space, time, reality and selfhood are woven into and embodied by one of the novel’s main characters, Periathai. Periathai attains the highest form of Hindu identity, Atman or True Self through spiritual knowledge, rituals, and self-reflexivity. This article suggests adherence to Hinduism provides the Malaysian Indians the agency to transcend the corporeal and physical realms, deconstruct the normative view of Hinduism as an ethnocentric religious nostalgia for India, and challenge the idea that religion further aggravates the Malaysian Indian sense of marginalization and displacement.